SEEKING TIME WITHIN TIME: EXPLORING THE TEMPORAL CONSTRAINTS OF WOMEN TEACHERS’ EXPERIENCES AS GRADUATE STUDENTS AND NOVICE RESEARCHERS - Mitton Kukner, Jennifer (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2014)
The primary focus of this qualitative study is an inquiry into three female teachers’ experiences as novice researchers. Over the course of an academic year I maintained a focus upon participants’ research experiences and their use of time as they conducted research studies. Delving into the temporal constraints that informed participants’ research experiences provided insights into competing demands shaping their understanding of research. In light of current performance accountability measures monitoring the ways teachers are using their professional time, this study provides new ways to consider the multiple challenges and gendered inequities female teachers are navigating in their efforts to professionally develop and learn. À LA RECHERCHE DU TEMPS DANS LE TEMPS: EXPLORATION DES CONTRAINTES TEMPORELLES VÉCUES PAR LES ENSEIGNANTES COMME ÉTUDIANTES GRADUÉES ET NOUVELLES CHERCHEURES Cette recherche qualitative analyse principalement les expériences vécues par trois enseignantes comme nouvelles chercheures. Au cours d’une année scolaire, j’ai porté mon attention sur les expériences de recherches des participantes et sur leur utilisation du temps lorsqu’elles menaient leurs recherches. Chercher à comprendre les contraintes temporelles qui influencent la démarche de recherche des participantes m’a offert un regard nouveau sur les demandes multiples qui façonnent leur compréhension de ce qu’est la recherche. Dans le contexte des mesures d’imputabilité actuelles, la manière dont les enseignants utilisent leur temps professionnel est étroitement surveillée. Tenant compte de ces mesures, ce projet de recherche révèle de nouvelles manières d’aborder les divers défis et les inégalités liées au genre auxquels les enseignantes font face, dans leurs efforts de développement et d’apprentissage professionnels.